Elevation of natural vulnerability in the karst aquifers (case study: karst aquifers of Sheshpier and Borgan, Fars province) - Mehdi kashefi; mojgan entezari; maryam Jafari Aghdam (تحقیقات کاربردی علوم جغرافیایی)
vulnerability is considered as an inherent talent of underground water system that depending on the sensitivity of the system to anthropogenic effects. Natural vulnerability is based on the geomorphologic features of surface karst, type and level of aquifer recharge and hydrodynamic aquifer karstic aquifer in Fars province is the most important source of water supply for the supplement of drinking water of communities in the province, which are prone to pollution due to the natural conditions of the region and human activities. karstic aquifer of Shispir and Borghan plays a vital role in supplying drinking and agricultural water around them. The aim of this study is to estimate the natural vulnerability karstic aquifer of Shispir and Borghan using the proposed model of Cast action 620, and prioritize the level of aquifer in the field of conservation measures and provide management solutions in order to better protect them in this model. To prepare a natural vulnerability map are used geological maps, soil, vegetation, digital elevation model (10 meter) and precipitation statistics of meteorological stations and vulnerability map is evaluated as three factors of C, O, p. In the end, the region in terms of damage in five levels was classified in very high, high, low, low and very. The results of the COP model show the natural vulnerability of the region is high. In addition, the amount of vulnerability in the two upper and upper floors of this region is about 47 % where is the highest coverage area of that region of Shisper aquifer. The results of this study show the efficiency of the proposed methods by Cast Action 620 to detect and protection of groundwater resources from vulnerabilities and natural pollution.